Direct conversion of natural gas into COx-free hydrogen and MWCNTs over commercial Ni–Mo/Al2O3 catalyst: Effect of reaction parameters - Ahmed E. Awadallah; Fatma Kh. Gad; Ateyya A. Aboul-Enein; Mahmoud R. Labib; Ahmed K. Aboul-Gheit (Egyptian Journal of Petroleum)
A commercial hydrotreating nickel molybdate/alumina catalyst was used for the direct conversion of natural gas (NG) into COx-free hydrogen and a co-valuable product of multi-walled carbon nanotubes (MWCNTs). The catalytic runs were carried out atmospherically in a fixed-bed flow reactor. The effect of reaction temperature between 600 and 800 °C, and dilution of the NG feed with nitrogen as well as pretreatment of the catalyst with hydrogen were investigated. At a reaction temperature of 700 °C and dilution ratio of NG/N2 = 20/30, the optimum yield of H2 (∼80%) was obtained with higher longevity. However, using the feed ratio of NG/N2 = 30/20, the optimum yield of MWCNTs was obtained (669%). X-ray diffraction pattern for the catalyst after the reaction showed that the MWCNTs were grown on the catalyst at all reaction temperatures under study. TEM pictures revealed that the as-grown MWCNTs at 600, 650 and 800 °C are short and long with a low graphitization degree. At 700 °C a forest of condensed CNTs is formed, whereas both carbon nanofibers and CNTs were formed at 750 °C.